Late Cenozoic Glaciations in Patagonia and Tierra del Fuego: an up-dated review - Rabassa, Jorge Oscar; Coronato, Andrea Maria Josefa; Martínez, Oscar Alfredo (Biological Journal of the Linnean Society)
The Patagonian glaciations developed from the latest Miocene (c. 6 Ma) in multiple events of varied duration and intensity. Most of the present glacial landscape is the result of the glacial modelling during the Pleistocene, since the Great Patagonian Glaciation (GPG; c. 1 Ma). The Patagonian Andes were covered by a continuous mountain ice sheet, from 37°S to Cape Horn (56°S), in at least five major glaciations over more than 15 cold events over the last million years. Before GPG, the glaciers were restricted to isolated ice caps along the mountain ranges. The present drainage network was developed after the Last Glacial Maximum [LGM; c. 25 calibrated kiloyears before present (cal. ka bp)], particularly those cases with drainage reversal, when the glaciers began to melt as a result of global climatic changes. The environmental impact of glaciations extended not only all over Patagonia, but to the Pampas as well. Las glaciaciones patagónicas se desarrollaron desde el final del Mioceno (ca. 6 Ma) en múltiples eventos, de variada duración e intensidad. La mayoría del paisaje andino actual es el resultado del modelado glaciario durante el Pleistoceno, desde la Gran Glaciación Patagónica (GGP; ca. 1 Ma). Los Andes Patagónicos fueron cubiertos por un manto de hielo de montaña continuo, desde 37°S hasta el Cabo de Hornos (56°S) a lo largo de por lo menos 5 glaciaciones mayores durante más de 15 eventos fríos en el último millón de años. Antes de la GGP, los glaciares estaban restringidos a casquetes glaciarios aislados a lo largo de las cadenas montañosas. El sistema de redes de drenaje actual, en especial en lo que hace a la inversión del drenaje, se desarrolló luego del Último Máximo Glacial (UMG; ca. 25 cal. ka A.P.), cuando los glaciares comenzaron a retirarse debido a cambios climáticos globales. El impacto ambiental de las glaciaciones se extendió, no sólo a toda la Patagonia, sino también a la región pampeana. Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...